THE REASON OF NASAL OBSTRUCTION AND THE WAYS OF IT’S ELIMINATION - Подовжній, О.Г. (World of Medicine and Biology, 2015)
Nasal septum deviations significantly change the direction of airflow.On the injured part there are bones or cartilaginous bulges in the form of a crest or a spike.The reason for chronic rhinitis can be nasal septum deviations, imperforation of nasal cavity synechia, polypous formations of the nasal cavity. In case of nasal obstruction, especially, in long period of time the need meticulous examination. First of all, it must be endoscopic, X-ray, examination and Computer scan. If mycetoma is mistrusted it is necessary to perform magnetic resonance image. The rhinosugery must be performed in early period to prevent systemic changes in organism. It is recommended to the patients with labored nasal breathing or on condition of development of pathologies caused by the action of the thorn or spike.